PONDD: an online platform for printing-on-demand and delivery of daily press, magazines and books - Konstantinou, Nikolaos; Papaioannou, Evi; Kaklamanis, Christos (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Motivated by difficulties experienced in the distribution of printed press, mainly daily press, i.e., newspapers, but also sometimes of periodical press, i.e., magazines, or even books, we designed and developed PONDD, an online platform for printing-on-demand and delivery of daily press, magazines and books. PONND can serve as an innovative service which can directly bring together readers and publishers via printing points, like for example kiosks or mini markets. Readers can select their desired newspaper, magazine or book, define their desired features for the print-out (e.g., single/duplex, colored/black&white) and choose an available printing point nearby for serving their requests, i.e., for picking-up or having delivered to them their selected newspaper, magazine or book. PONDD is easy-to-use and responsive offering a comprehensive set of well-defined functionalities. In our current era, information is a critical resource and the internet should be exploited not only as a modern information distribution channel but also as a backbone for supporting the continuation of free, undisturbed and uninterrupted distribution of traditional printed press.